2020
DOI: 10.1136/bmjqs-2019-010368
|View full text |Cite
|
Sign up to set email alerts
|

Time series evaluation of improvement interventions to reduce alarm notifications in a paediatric hospital

Abstract: Background10The Joint Commission identified inpatient alarm reduction as an opportunity to improve patient safety; enhance patient, family and nursing satisfaction; and optimise workflow. We used quality improvement (QI) methods to safely decrease non-actionable alarm notifications to bedside providers.MethodsIn a paediatric tertiary care centre, we convened a multidisciplinary team to address alarm notifications in our acute care cardiology unit. Alarm notification was defined as any alert to bedside provider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…In line with previous publications, respondents reported that the high rate of false alarms interrupted patient care and demanded a hospital SOP for alarm management [ 21 ]. In several studies, implementation of such an alarm management SOP reduced the alarm rate significantly [ 21 , 22 ]. Further temporal analysis of the alarm frequencies per sensor as previously described [ 23 ] may find causes for the high rate of false alarms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with previous publications, respondents reported that the high rate of false alarms interrupted patient care and demanded a hospital SOP for alarm management [ 21 ]. In several studies, implementation of such an alarm management SOP reduced the alarm rate significantly [ 21 , 22 ]. Further temporal analysis of the alarm frequencies per sensor as previously described [ 23 ] may find causes for the high rate of false alarms.…”
Section: Discussionmentioning
confidence: 99%
“…Our survey results show that ICU staff members are open to learning more about technology and are even willing to support product development in some cases. Thus, a clinical data scientist with formal medical training could be part of the ICU team as well as the product development team alongside engineers from a medical manufacturer [ 22 , 37 ]. This transdisciplinary approach should be piloted in further studies, to assess the effects on mutual exchange and innovation potential.…”
Section: Discussionmentioning
confidence: 99%
“…These smarter algorithms are currently being created through consultation with clinical experts. 40 However, in the future, such algorithms could also include approaches using machine learning and artificial intelligence techniques, making use of real patient data in offline big datasets and then applied to live patient devices, but only after appropriate safety testing. 20,25,27 When all available parameters from all available devices are combined into a system of comprehensive alarms, these can be better prioritised within the work process of the healthcare provider, resulting in substantially fewer but more meaningful alarms (see Figures 2 and 3).…”
Section: Comprehensive Alarmsmentioning
confidence: 99%
“…These smarter algorithms are currently being created through consultation with clinical experts. 40 However, in the future, such algorithms could also include approaches using machine learning and artificial intelligence techniques, making use of real patient data in offline big datasets and then applied to live patient devices, but only after appropriate safety testing. 20,25,27…”
Section: Comprehensive Alarmsmentioning
confidence: 99%
“…In this issue of BMJ Quality and Safety, Pater et al 12 report the results of a comprehensive multidisciplinary alarm management QI project executed over 3½ years in a 17-bed paediatric acute care cardiology unit. The primary project goal was to reduce alarm notifications from continuous bedside monitoring.…”
mentioning
confidence: 99%